International Capital Markets, 1998. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This year's capital markets report provides a comprehensive survey of recent developments and trends in the advanced and emerging capital markets, focusing on financial market behavior during the Asian crisis, policy lessons for dealing with volatility in capital flows, banking sector developments in the advanced and emerging markets, initiatives in banking system supervision and regulation, and the financial infrastructure for managing systemic risk in EMU.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet